Art in action cultivating culture and industries in a cultural and creative hub through an experience- centered approach to human-building interaction - Natanauan, Kylla Eunice B. (College of Architecture, University of the Philippines Diliman, 2025)
This study explores how the challenges faced by the Filipino creative industries may be addressed through a designed cultural and creative hub applying an architectural approach anchored on Human-Building Interaction (HBI). The local creative sector, with its rich cultural diversity and artistry, holds great potential in strengthening the country’s economy and identity. Despite this, its development is constrained by numerous challenges manifested in its fragmented structure, weak engagement with the public, and the lack of a deeper understanding of the sector’s significance, resulting in the limited opportunities for both the creatives and their audiences to collaborate and interact. As such, the project seeks to provide a synthesized architectural program merging creative industries through the concept of Design Thinking, and to strengthen the public’s involvement in the sector following the concepts of place. Given its already existing creative community, Escolta Street was chosen as the project’s site to strengthen the link between diverse creative spaces. Preliminary cultural mapping of Escolta, thematic analysis, content analysis, and case studies were done to determine the intersections between different creative processes, the existing cultural and creative spaces in Escolta and their distinct features, and to develop a catalog of applicable interactive strategies to the proposed space. The overall data gathered from these led to design concepts revolving around the main ideas of collaborative creativity, experience, and creative placemaking. With these, the proposed design features the integration of local culture to facilitate interdisciplinary art collaboration and community engagement and the introduction of new interactive architectural interventions to elicit creative placemaking.